Wpływ Szerokości Walcowo Giętego Pasma na Moment Zginający w Stanie Plastycznym - Klepaczko, J. (Engineering Transactions, 1962)
The present paper is concerned with the results of an investigation of strips of various width subjected to cylindrical bending. The work is confined to rectangular profiles. On the basis of the results obtained it is found that the bending process can be described by a surface in a three-dimensional space using M/W, g/2go, b/g as coordinates, where M is the bending moment, W-the section index, g- the thickness of the strip, b- its width and 9o the radius of the middle layer.The deformation of the cross-section of the strip is analysed for large and small values of b|g (the relative width of the strip). The paper presents also an analysis of the influence of the width on the bending moment per unit width of the strip. The maximum values of (b[g)o have been found experimentally for two materials: soft steel and brass. Above these values the bending moment per unit width of the strip remains constant. For mild steel we have (b|g)o F 20 and for brass (b/g)o ~ 10. On the basis of the known solutions mathematical relations are proposed to describe the bending process of the strip for plane strain, and assuming, the power law of strain hardening ε = CoM - Co.For the value b/g < (b/g)o is given the experimental coefficient K of weakening of the bent strip in relation to a strip with infinite width. The graphoanalytic method proposed enables us to obtain the M-1/o diagram for large vatures. This method has been verified experimentally for brass up to the value of g/200 = 0,3 with the degree of accuracy of the order of 5%.